IMPLEMENTASI PERATURAN DAERAH KABUPATEN SUMBAWA NOMOR 10 TAHUN 2012 TENTANG RENCANA TATA RUANG WILAYAH DALAM MENGATASI PENYALAHGUNAAN LAHAN YANG MERUSAK EKOLOGI (STUDI KASUS: PULAU BUNGIN, KECAMATAN ALAS, KABUPATEN SUMBAWA) - Leni Nurul Kariyani (Nusantara Hasana Journal, 2025)
This study examines the implementation of Regional Regulation No. 10 of 2012 of Sumbawa Regency on Spatial Planning (RTRW) in addressing land misuse that causes ecological degradation. The research focuses on the effectiveness of spatial planning policy implementation in coastal areas, with a case study on Bungin Island, Alas District a highly populated small island experiencing land pressure due to traditional sea reclamation practices. The study employs a literature review method, analyzing relevant regulatory documents, local government reports, and academic studies related to spatial planning and ecological impacts. The findings indicate that the implementation of the RTRW policy has not been fully effective due to weak supervision, limited spatial data, and low public awareness regarding environmental balance. Nevertheless, the local government has strengthened its efforts through the development of Detailed Spatial Plans (RDTR), the application of Geographic Information Systems (GIS), and the promotion of green development programs that integrate conservation and community participation. The study concludes that effective collaboration among the government, communities, and academic institutions is essential to achieve sustainable spatial governance that preserves ecosystems while supporting the well-being of the Sumbawa community.